DEIKSIS DALAM NOVEL SUNYI ADALAH MINUMAN KERAS KARYA SAPARDI DJOKO DAMONO DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Wibowo, Pangestu Adi; Rizkian, Muhammad Fahmi (Universitas Indraprasta PGRI, 2024)
This research aims to find out and vocalise the use of deixis contained in the novel Sunyi adalah minuman keras by Sapardi Djoko Damono and its implications for Indonesian language learning and the scope of the article's content; the research method uses descriptive qualitative, the data recording method uses the simak catat method, the data validity check uses triangulation techniques. The results of the research found a total of 678 deixis with the following description, persona deixis amounted to 332 findings percentage of 49%, place deixis amounted to 214 findings percentage of 32%, and time deixis amounted to 132 findings percentage of 19%. The use of deixis in the novel sunyi is liquor is dominated by persona deixis. The implication for Indonesian language learning is in KD 4.5 understanding the linguistic rules of procedural texts, namely pronouns (pronomina).